Deltamethrin Contact Exposure Mediated Toxicity and Histopathological Aberrations in Tissue Systems of Public Health Importance Cockroach Species Periplaneta americana and Blattella germanica - Dhiman, Sunil; Yadav, Kavita; Acharya, B. N.; Nagar, D. P.; Rao Ghorpade, Rama (Frontiers in Physiology, 2022)
Cockroach species Periplaneta americana and Blatella germanica potentially survive in locations close to human activity. Besides spoiling food material, cockroaches also transfer pathogens of different diseases among human. Since the insecticides have been used extensively to control cockroaches, information on their insecticide susceptibility and toxicity at cellular level may be crucial. In the study, deltamethrin toxicity as well as the deltamethrin-mediated cytomorphological changes in brain, ovary and midgut of the two important cockroach species has been assessed. Different concentrations [0.00025% (0.0025mg/ml), 0.0025% (0.025mg/ml), 0.025 (0.25mg/ml), 0.25% (2.5mg/ml), 0.5% (5mg/ml), 1% (10mg/ml)] of deltamethrin in acetone were used to expose test species in WHO bottle assay and knockdown and delayed mortality was observed. Brain, ovary and gut were dissected (for 0.25%, 0.5% and 1% concentration exposure) for microscopic analysis. Deltamethrin exposed cockroaches and dissected tissues were used to estimate deltamethrin using HPLC. At 0.00025% (lowest concentration), the percentage knock-down observed was 66.7% for P. americana and 80% B. germanica respectively (R2= 0.78; p=0.0001) in 1 hr. KDT50 value was found to be 8.7 min (95% CI: 7.3-10.2), while KDT99 was 20.7 min (95% CI: 16.0-35.7) in P. americana at 1% concentration. Whereas, the KDT50 and KDT99 values for B. germanica were 7.4 min (95% CI: 5.4-9.1) and 27.4 min (95% CI: 18.2-80.0) at similar concentration. LD50 and LD95 values were 0.0006 % (95% CI: 0.00-0.001) and 0.034% (95% CI: 0.013-0.49) respectively for P. americana, while these values were 0.0005 (95% CI: 0.00-0.001) and 0.04 (95% CI: 0.01-0.23) for B. germanica. Exposure to 1% deltamethrin induced considerable toxic effect in the epithelial cells in the midgut. HPLC estimated 0.21±0.05 mg (95% CI - 0.18-0.25; CoV 23.9%) deltamethrin in P. americana post 1% exposure. Even short term exposure of low concentration of deltamethrin displayed immediate knockdown and delayed mortality in both the test species. Considerable histological damage was observed iat 1% exposure. In India, resistance to deltamethrin may have been reported among different insects due its extensive use, however the formulations such as insecticide paints, attractant baits etc. developed using deltamethrin as active ingredient could be useful in cockroach control operations.